(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Overhead power lines (OPL) form the basis of a power grid. Reliable energy supply depends on no-failure operation of these long-length elements of energy infrastructure. More than 12,000 km out of 45,000 km of OPL in Pskov region (Russia) pass through forests. This study investigates the possibilities of using satellite-sensing data to assess the conditions of corridors for OPL with different voltage levels. Authors evaluated compliance of actual data with requirements of national standards. The dynamics of vegetation and local topography based on synthetic aperture radar data and multispectral images were taken into account.